PENGELOLAAN LIMBAH CAIR TAPIOKA DI LAMPUNG (Tapioca Waste Water Treatments in Lampung) - Oktarina, Eva (Baristand Industri Banda Aceh, 2015)
Lampung is the biggest producer cassava in Indonesia in 2010 until 2014. In 2013,Lampung produce 9.633.560 ton cassava, which mostly used as tapiocas raw material. Waste water fromtapioca industry has high organic content that can pollute environment. In fact, the organic waste can stillbe processed into other products that are more usable such as methane, nata de cassava, biosurfactant,Microbial Fuel Cell (MFC), bioethanol, and Poly Hydroxyl Alkanoat (PHA). Therefore, waste watertreatments method needed so tapioca industry can optimally worked without threatened environment. Thisarticle aim is to explore waste water treatments for tapioca industry by sustainability integrated wastewater management. So it can assist tapioca industry in environment and economic aspect. Good wastemanagement is also expected for increasing utility value and economical value of tapioca waste water.